NIMG-29. ELEVATION OF GLUTAMINE AND CITRATE BY MR SPECTROSCOPY IS AN IMAGING BIOMARKER OF RAPID CELL PROLIFERATION IN GLIOMAS. (12th November 2021) - Tiwari, Vivek; Askari, Pegah; Maher, Elizabeth; Choi, Changho
Abstract: Prior studies suggested glutamine metabolism in cancers may be altered to meet the high demands of nucleotide biosynthesis in cancers. We conducted 1H MR spectroscopy in 18 glioma patients and analyzed the metabolic data together with post-gadolinium MRI and cell proliferation rate (MIB-1 label index). The optimized MRS (TE 97 ms PRESS) provided well discernible signal of glutamine at 2.45 ppm and a negative-polarity signal of citrate at 2.6 ppm, without considerable overlaps with neighboring signals. The 18 patients had biopsy-proven anaplastic gliomas or glioblastomas. Concurrent elevation of glutamine and citrate was identified in 15 gliomas. These gliomas presented with enhancement in post-gadolinium MRI, indicative of broken blood-brain barrier (BBB). The 15 gliomas were grouped as subset-1 while the other 3 gliomas that had elevated citrate without elevation of glutamine were grouped as subset-2. Citrate level was significantly different between the two subsets of gliomas (1.4+/-0.5 vs. 1.6+/-0.4 mM). However, subst-1 had significantly higher choline (4.7+/-1.8 vs. 1.6+/-0.3 mM, p< 0.01) and higher MIB-1 compared with subset-2. Given that choline is a cellularity marker, a finding of high choline and high MIB-1 with elevation of glutamine and citrate suggests that the tumors have high tumor cellularity and cell multiplication competence. Of the 18 gliomas, 13 were IDH mutated with elevated 2HG. The glutamine and citrate levels in IDH-mutant gliomas were not significantly different from those in IDH wildtype gliomas. In conclusion, high-grade gliomas undergo a metabolic rearrangement of concurrent elevation of glutamine and citrate to attain malignant characters such as high cellularity, rapid cell proliferation, and BBB breakdown. IDH mutant and IDH wildtype gliomas may share a common metabolic rearrangement of glutamine-mediated citrate elevation to attain malignancy. Measurements of glutamine and citrate may serve a potential imaging biomarker for aggressive gliomas.